Promised Lands : New Jewish American Fiction on Longing and Belonging. - Rubin, Derek, 1954- (Brandeis Series in American Jewish History, Culture, and Life & HBI Series on Jewish Women., 2010)
An anthology of previously-unpublished stories by leading young Jewish writers that explore the idea of the Promised Land.